2020
DOI: 10.5194/egusphere-egu2020-12490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous dynamic rupture modeling of 2017 M 5.4 Pohang, South Korea, earthquake, using the slip-weakening friction law

Abstract: <p>An M 5.4 earthquake occurred in the southeastern part of the Korean Peninsula in 2017. It is an oblique thrust event that occurred at a relatively shallow depth (~ 5 km) although it did not create coseismic surface rupture. A coseismic slip model was successfully obtained by inverting the ground displacement field extracted by the InSAR data (Song and Lee, 2019). In this study, we performed spontaneous dynamic rupture modeling using the slip weakening friction law. The static stress drop distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, there was a significant increase in the average frequency to 70.6 after 1999, following the initiation of digital recording for earthquake monitoring [15]. This notable rise can be attributed, in part, to the occurrence of major earthquakes in Gyeongju (M W 5.5, 2016) and Pohang (M W 5.5, 2017) [16,17]. These events led to heightened concerns about earthquake vulnerability on the Korean Peninsula and to increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a significant increase in the average frequency to 70.6 after 1999, following the initiation of digital recording for earthquake monitoring [15]. This notable rise can be attributed, in part, to the occurrence of major earthquakes in Gyeongju (M W 5.5, 2016) and Pohang (M W 5.5, 2017) [16,17]. These events led to heightened concerns about earthquake vulnerability on the Korean Peninsula and to increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…Elements near the edges of the cracks weaken the grain boundaries. [ 26–29 ] Song et al suggested that the formation of Si and Mn oxides at the interface of the oxide layer and the steel has been also associated with intergranular corrosion inducing cracking during forging in Si‐containing steel. [ 26 ] Bitterlin et al found that Cr–Mn–V oxides existed in crack propagation during normalizing heat‐treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26–29 ] Song et al suggested that the formation of Si and Mn oxides at the interface of the oxide layer and the steel has been also associated with intergranular corrosion inducing cracking during forging in Si‐containing steel. [ 26 ] Bitterlin et al found that Cr–Mn–V oxides existed in crack propagation during normalizing heat‐treatment process. Thus, they suggested that the fragilization brought to the material by the formation of these oxides is probably one of the root causes for crack growth in a medium‐carbon low‐alloy steel.…”
Section: Introductionmentioning
confidence: 99%